Information Warfare and Organizational Decision-Making. - Kott, Alexander (Artech House information warfare library., 2006)
Unconventional warfare is now conventional, requiring the military to organize in new ways that can rapidly respond to unprecedented battlefield challenges. Cutting-edge computing is helping military planners create original organizational structures able to adapt to ever-changing strategies and tactics. The computational techniques in this book provide practical solutions for organizing and commanding military operations, gathering intelligence, deploying antiterrorism measures, and securing information. The book covers artificial intelligence, game and control theory, and cognitive modeling.